Multidisciplinary approach for anatomical correction and diastema closure with laminates veneers – a clinical report - Llerena-Icochea, Alfredo; Velo, Marilia; Borges, Ana Flávia Sanches; Mondelli, Rafael; Furuse, Adilson (Brazilian Dental Science, 2020)
Objective: multidisciplinary treatment has become increasingly common in dental offices and this treatment strategy is based on the achievement of a healthy, harmonious, and pleasant smile. In addition, the development of new ceramic systems and the possibility of making indirect restorations with a low thickness, such as laminates veneers, allowed combining highly satisfactory aesthetic properties, preserving the dental structure through minimal wear. Case report: this paper describes a multidisciplinary approach involving periodontics and restorative dentistry for the successful, functional, and aesthetic treatment in an adult patient. The digital smile design was performed as a guide to plan the clinical case considering factors such as tooth inclination and position, golden proportion, tooth size and shape. Discussion: based on these concepts, the present work reports, through a clinical case, the restoration of aesthetics and function with ceramic laminates veneers in lithium disilicate, in the case of anatomical correction and diastema closure. Conclusion: overall, the multidisciplinary treatment plan demonstrated to have greater advantages both for the aesthetics and function of the patient, as well as for the work team. During the 24-month follow-up, this case presented great functional and aesthetics results.KEYWORDSCeramic veneers; Aesthetic dentistry; Multidisciplinary treatment.